External support and personal agency - young persons’ reports on recovery after family-based inpatient treatment for anorexia nervosa: a qualitative descriptive study - Jan-Vegard Nilsen; Trine Wiig Hage; Øyvind Rø; Inger Halvorsen; Hanne Weie Oddli (Journal of Eating Disorders, 2020)
Abstract Background Recommended treatment for adolescent anorexia nervosa (AN) is usually family-based and an overarching treatment aim is to empower the parents to manage the difficult meals and aid their child toward recovery. While family-based treatment prioritize collaborating with the parents, understanding the young persons’ views on recovery is also important. Understanding the young person’s views and ideas is relevant as this may facilitate the therapeutic alliance and thus aid the therapeutic process. The purpose of the present study was to investigate the reflections of young persons with a lived experience of anorexia nervosa, and what factors they consider important for the recovery process. All participants had been provided with a family-based inpatient treatment program, a program inspired by the core features of outpatient family-based treatment. Methods Participants (n = 37) presented with an extensive treatment history, including outpatient and inpatient treatment for AN. Interview transcripts were analyzed by applying a predominantly inductive thematic approach to generate themes across participants. Results The qualitative analysis generated a thematic structure entailing three levels. The superordinate theme, “Recovery is a long and winding journey: recognizing the need for support and highlighting the need for action”, captured three main themes, “Realizing you have a problem”, “Being involved in important relationships”, and “Giving treatment a real chance”. Conclusions Our results demonstrated that although young persons with a lived experience of anorexia nervosa recognized the importance of support from others, they placed a distinctive emphasis on self-responsibility and determination. We recommend clinicians working within the recommended family-based treatment frameworks be curious about young patient’s subjective perspectives of the recovery process, as connecting with their views can potentially strengthen therapeutic relationships and facilitate change. Plain English summary Recommended treatment for adolescent anorexia nervosa is usually family-based. These recommendations are supported by decades of research. In family-based treatment the overarching aim is to empower the young person’s parents to manage and take charge of the difficult situation caused by the eating disorder. As recommended family-based treatments usually prioritize collaborating with the parents, it is important to be curious on the adolescents own views of what is regarded as important for the recovery process. The present study offers insights into factors considered important to the recovery process by young persons with lived experience of AN. Although voicing the importance of enlisting support from families, friends, and loved ones, the young participants distinctly emphasized their own responsibility, motivation and self-determination as critical factors for recovery. Inspired by our findings, we recommend that clinicians address the young patient’s own preferred ideas for recovery during treatment.